Optical and magnetic control of electron spins in tailored semiconductors - Langer, Lukas (Technische Universität Dortmund, 2016)
The thesis explores three different approaches for the reciprocal manipulation of polarized light and electron spins in semiconductors. In the first approach, the direct optical orientation and alignment of Mn electron spins in CdMnTe spin glass is demonstrated. The second approach uses a GaAs-based ferromagnet/semiconductor hybrid structure to demonstrate dynamic spin polarization. The effect is explained by spin-dependent tunneling of electrons from the semiconductor quantum well into the ferromagnetic layer. In the third approach, the spontaneous and stimulated photon echoes from trions in a quantum well are exploited. The application of a transverse magnetic field allows the transfer of optically excited coherence into the long-lived spin state of the resident electron and a subsequent retrieval.
Keywords: Optik; Halbleiter; Elektronenspins; Photonenecho; Ferromagnet/Halbleiter Hybrid Struktur; CdMnTe; 530; Elektronenspin; Ferromagnetikum; Photonenecho; Tunneleffekt